Pattern of Pediatric Uveitis at a Tertiary Referral Institute in North India. (3rd April 2018) - Gautam, Natasha; Singh, Ramandeep; Agarwal, Aniruddha; Yangzes, Sonam; Dogra, Mohit; Sharma, Ashok; Bansal, Reema; Gupta, Vishali; Dogra, Mangat R.; Gupta, Amod
ABSTRACT: Purpose : To report the pattern of pediatric uveitis in a tertiary care referral center in North India. Methods : In a retrospective study, records of pediatric uveitis cases presenting at our center between 1996 and 2015 were reviewed for demographic data, anatomic distribution, and diagnosis. Results : Out of 9600 patients with uveitis, 369 children (3.84%; age ≤16 years; males: 54.20%) were included in the study. Anterior uveitis was the commonest presentation ( n = 158; 42.81%), followed by posterior uveitis ( n = 102; 27.64%). Uveitis was bilateral in 57.18% ( n = 211). Infective etiology was seen in 99 children, of which tuberculosis was the commonest cause ( n = 55; 14.91%). Among non-infectious etiologies, juvenile idiopathic arthritis (JIA) was the commonest cause ( n = 59; 15.99%). Conclusions : While anterior uveitis is the commonest uveitis in children, our cohort reported a high number of posterior uveitis cases compared to previous studies. Tuberculosis and JIA were the commonest causes of pediatric uveitis.